First record of genus Phlyctaenopora in South Pacific waters - Kelly, Michelle (Zootaxa, 2021)
Four species of Phlyctaenopora Topsent, 1904 (Demospongiae Sollas, Poecilosclerida Topsent, Mycalidae Lundbeck) are recognised today (Van Soest et al. 2021a) (Table 1): two Atlantic Ocean species in subgenus Phlyctaenopora [type species P. (P.) bitorquis Topsent, 1904, from the Azores; P. (P.) halichondrioides van Soest & Stentoft, 1988, from Barbados]; and two Southern Hemisphere species in subgenus Barbozia Dendy, 1922: P. (Barbozia) primitiva Dendy, 1922, from the Seychelles, and P. (B.) bocagei Lévi & Lévi, 1983, from New Caledonia. Here we describe a new species of Phlyctaenopora from Wanganella North in International Waters on the West Norfolk Ridge, northwest of New Zealand. Phlyctaenopora (B.) spina sp. nov. provides a first record of the genus in the South Pacific, providing further confirmation of the integrity of the subgenus Barbozia.